Tantangan Ekspor Produk Farmasi PT “X”: Sebuah Studi Kualitatif - Ignatia Lumen Christinopa; Tampubolon, Lamtiur Hasianna; Prasadja, Heru (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This study aims to identify the challenges faced by PT "X" in exporting pharmaceutical products. The research employs a descriptive qualitative approach through in-depth interviews with Export Specialists, Export Customers, and Export-Import Managers. The findings reveal that the main challenges include navigating international regulations, managing logistical complexities, adjusting products to meet buyer preferences, political and economic risks in destination countries, currency fluctuations, competitive pricing, and building robust distribution networks. Regulatory navigation involves adapting documents such as dossiers and stability requirements for Zone IVB. Logistical complexities pertain to shipping goods under specific conditions, such as cold chains, and external obstacles like lockdowns. Product adjustments involve changes in packaging design, the use of local languages, and compliance with shelf-life requirements. Political and economic risks include fluctuations in demand and payment issues from buyers. For pricing, challenges arise from unexpected costs and price comparisons with competitors. Distribution constraints stem from limited control over third-party-managed channels. PT "X" employs various mitigation strategies, including technology-based logistics management, intensive communication with partners, and careful selection of distribution partners. This study provides a concrete overview of the challenges faced by pharmaceutical companies in export activities and strategic measures to enhance competitiveness in international markets.